Neotypification of Lepidagathis bandraensis (Acanthaceae) - Tiwari, U.; Ravikumar, K. (Rheedea, 2013)
A neotype is designated here for Lepidagathis bandraensis Blatt. (Acanthaceae). Besides, this species is reported here as a new distributional record to flora of Gujarat.